1992
DOI: 10.1002/j.2161-0045.1992.tb00361.x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Influence of Two Computer‐Assisted Career Guidance Systems: DISCOVER and SIGI

Abstract: Perceptions of expertness, attractiveness, and trustworthiness of computer-assisted guidance systems, as measured by an adapted version of the Counselor Rating Form (CRF), were compared for 107 college students in two treatment conditions (DIS-COVER and SIGI) and a computer imaging control condition. Findings showed that students in the DISCOVER and SIGI conditions had more positive perceptions of the attractiveness of systems than those in the computer imaging group. In a review of related studies using the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Therefore, counselors engaged in career counseling should have the background that prepares them to operate from a well-researched career counseling theory/approach, such as CIP, and should be capable ofpresenting the rationale for the way in which CACGs fit into that perspective. Practitioners interested in learning more about how to integrate CIP theory with the use ofCACGs are referred to Sampson et al (1992). A third implication is the important role oforientation to CACGs.…”
Section: Implications For Career Counselingmentioning
confidence: 99%
“…Therefore, counselors engaged in career counseling should have the background that prepares them to operate from a well-researched career counseling theory/approach, such as CIP, and should be capable ofpresenting the rationale for the way in which CACGs fit into that perspective. Practitioners interested in learning more about how to integrate CIP theory with the use ofCACGs are referred to Sampson et al (1992). A third implication is the important role oforientation to CACGs.…”
Section: Implications For Career Counselingmentioning
confidence: 99%
“…Research indicates that CACG systems are most effective when used in conjunction with competent counseling (Eveland, Conyne, & Blakney, 1998;Sampson et al, 1992). They are frequently used in the context of a counseling relationship, although users commonly have access to the systems with little or no human intervention.…”
Section: Computer-assisted Career Guidance Systemsmentioning
confidence: 99%
“…Indeed, exactly the same career intervention has seldom been tested with different samples on different occasions. The current authors could find only one exception, entailing the computerized career guidance program entitled DISCOVER, which has been examined in at least three investigations (Fukuyama et al, 1988; Luzzo & Pierce, 1996; Sampson et al, 1992). Fukuyama et al, utilizing a convenience sample of students from a United States university, found that the DISCOVER program “had a positive effect on career self-efficacy and career decision making for undergraduate participants” (p. 61).…”
Section: Replication Of Career Intervention Studiesmentioning
confidence: 99%